Space 2000 Conference and Exposition 2000
DOI: 10.2514/6.2000-5173
|View full text |Cite
|
Sign up to set email alerts
|

An interstellar probe mission to the boundaries of the heliosphere and nearby interstellar space

Abstract: Abstract. NASA's Interstellar Probe Mission, which will travel to 200-400 AU using solar sail propulsion, will be the first spacecraft specifically designed to explore the outer solar system and sample the nearby interstellar medium. During the spring of 1999, NASA's Interstellar Probe Science and Technology Definition Team * developed a concept for a mission to be propelled by a solar sail that would travel to >200 AU in 15 years. A 400-m diameter solar sail accelerates the spacecraft to ~15 AU/year, approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…13. The local interstellar neighborhood, shown on a logarithmic scale from the sun to 10 6 AU [28]. XNAV can provide significant improvement over DSN-only navigation at distances beyond Jupiter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13. The local interstellar neighborhood, shown on a logarithmic scale from the sun to 10 6 AU [28]. XNAV can provide significant improvement over DSN-only navigation at distances beyond Jupiter.…”
Section: Discussionmentioning
confidence: 99%
“…A mission to investigate the Pioneer gravitational anomaly has been proposed, which would require accurate tracking of the spacecraft to distances far beyond Jupiter, measuring the acceleration of the spacecraft very precisely. XNAV could assist in providing more accurate navigation data than can be The Interstellar Probe mission would travel to a distance of about 400 AU from the Sun, exploring the Kuiper Belt, the boundaries of the heliosphere, and nearby interstellar medium [28]. The 550 AU mission to study the gravitational lens effect of the sun is indicated in the figure ("Gravity Lens" label) [29].…”
Section: Mars and Moon This Scenario Focuses On Navigation Atmentioning
confidence: 99%
See 1 more Smart Citation
“…The last two decades have seen an increased interest in utilizing the benefits of solar sailing and several missions have been designed specifically for its use. These include missions that provide early detection and warning of solar events (Heliostorm) 9 , missions to conduct detailed analysis of helioseismology and heliomagnetism (Solar Polar Imager) 10 , or mission to explore our local galactic neighborhood beyond the heliopause (Interstellar Probe) 11 .…”
Section: History Of Solar Sailingmentioning
confidence: 99%
“…Past concepts for such a mission have included the use of near-Sun powered gravity assists, with both chemical 6 and advanced high-thrust systems 9,10,11,12,13,14,15 , nuclear electric propulsion (NEP) 2,3,4,16,17 , and solar sails 18,19 . In this work, we detail the mission design studies for such a mission, dubbed the Innovative Interstellar Explorer (IIE) using radioisotope electric propulsion (REP) 20 .…”
Section: Introductionmentioning
confidence: 99%